2015
DOI: 10.5944/educxx1.13461
|View full text |Cite
|
Sign up to set email alerts
|

Differences in online study behaviour between sub-populations of MOOC learners

Abstract: Information was gathered about learners who were studying on repeat offerings in 2013-14 of six University of Edinburgh MOOCs on the Coursera platform. Two sources of information were used in this study: learner-contributed information about themselves and their study intentions collected in voluntary surveys, and data about learner behaviours, including performance on the courses, collected from the platform software during the MOOC deliveries. Three aspects of learner attributes and behaviours were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 3 publications
1
10
0
5
Order By: Relevance
“…In relation to the third research question, we found that learners who comment have similar demographic characteristics to those learners who complete more of the MOOC, and that there is a strong relationship between being a commenter and completing. These findings concur with previous research examining forum activity and retention (Balakrishnan & Coetzee, ; Breslow et al, ; Kizilcec et al, ; Woodgate et al, ). However, for most commenters, those who make just a few comments, the volume of comments they make has only a weak relationship with completion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In relation to the third research question, we found that learners who comment have similar demographic characteristics to those learners who complete more of the MOOC, and that there is a strong relationship between being a commenter and completing. These findings concur with previous research examining forum activity and retention (Balakrishnan & Coetzee, ; Breslow et al, ; Kizilcec et al, ; Woodgate et al, ). However, for most commenters, those who make just a few comments, the volume of comments they make has only a weak relationship with completion.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, it is not surprising that there have been many studies examining the factors associated with retention in MOOCs (Breslow et al, ; Cisel, ; Guo & Reinecke, ; Kizilcec, Piech, & Schneider, 2013; Palin, ), some of which have focused on the role of social interaction. Several studies have found that MOOC learners who post in discussion forums are less likely to drop out than those who do not (Balakrishnan & Coetzee, ; Breslow et al, ; Kizilcec et al, ; Woodgate, Macleod, Scott, & Haywood, ). Balakrishnan and Coetzee (), examining data from a Coursera MOOC, found that students who posted on a weekly basis were very unlikely to drop out, whilst those who did not post were more likely to drop out but not as likely as those who did not read posts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessments in MOOCs may serve different goals, due to the open nature of the courses, such as selftesting or formal assessment for course credit (Woodgate, Macleod, Scott, & Haywood, 2015). With the massive number of participants in a course, conducting assessments by the instructors is impossible (Glance et al, 2013;Sandeen, 2013;Suen, 2014) and different models of assessments are evolving, including: automated quizzes, peer assessments, and self-assessments.…”
Section: Background Moocs Learning Resourcesmentioning
confidence: 99%
“…MOOC research shows that MOOC learners are diverse in terms of cultural background and country of origin, online experience, education level, employment status and in their reasons for enrolling in a MOOC (Dillahunt, Chen & Teasley, 2014;Guo & Reinecke 2014;Woodgate, Macleod, Scott & Haywood, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%